The Accountability vs Transparency: Who is in Control in the Financial Management of Nonprofit Institutions? - Julaika, Janny; Wardhani, Nurhastuty Kesumo (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
The research aims to identify the influence of quantitative accountability, economic transparency, and internal control on the monetary control of non-profit organizations operating in network disciplines in Indonesia. The combination of accountability and transparency in financial management and accountability systems is used as a theoretical framework. The design/methods/techniques to be used in the study include quantitative methods. Data collected through the distribution of Google forms and manual questionnaires to respondents and the test tool used by Partial Least Square (PLS) based on financial accounting standards (ISAK) 35 proves that financial accountability and transparency systems affect Financial Management and Accountability. Accountability and transparency policies and practices are carried out. The results of this study are accountability has a significant effect on financial management, transparency has no significant effect on financial management and internal control has a significant effect on financial management. This research contributes to understanding the policy implementation and practice of liability and transparency in monetary control of non-profit groups, particularly in the Association environment, by demonstrating that the financial accountability system used today is aligned with applicable accounting standards. This research addresses the effect of economic taxation, economic surveillance, and price range transparency on monetary control. The results showed that the monetary responsibility of the organization using the traditional approach and not by ISAK 35 Accountability and Transparency developed so that it does not reflect management and accountability according to accounting standards. The financial position and cash flow statements show that there is no responsibility and the lack of transparency regarding financial management is proof of this.